Bamboo Management for Productivity Enhancement - Tripathi, Y. C.; Thakur, Ajay; Bhuyan, T. C. (Indian Forester, 2008)
India is one of the richest countries in Bamboo population covering 12.8% of the total forest land of the country. However, the yield per hectare is dismally low due to poor management, unscientific exploitation and low investment in raising preferred bamboo species. Very little attention has been paid until now to the management of natural bamboo stands and to ensure sustained supply of this raw material that result in constraining and reducing the potential benefits and value of bamboo applications. The current demand of bamboo for various purposes is estimated at 26.69 million tonnes as against the supply of 13.47 million tonnes. The average per hectare annual productivity of bamboo in India is about 1 MT/ha which is much less than the world's average. Low per hectare yield indicates poor management of existing bamboo plantations in forest and non-forest areas. It has been shown in case of some species that intensive cultural operations and scientific management of bamboo plantations can produce much higher yield. Establishment and management aspects of bamboo plantation for enhanced productivity are discussed in the paper.